Vein of Galen Aneurysmal Malformations in Pediatric Patients Submitted to Endovascular Treatment: Report of 3 Cases - Zimmermann, Amanda Cristina; Przysiezny, Bernardo; Giustina, Evelyn Della; Staedele, Guilherme Voltolini; Haas, Leandro José; Tutida, Letícia Saori; Camilo, Liz Caroline de Oliveira (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2021)
Objective To report three cases of vein of Galen aneurysmal malformation (VGAM) in pediatric patients treated at the hemodynamics lab of Hospital Santa Isabel (HSI) in Blumenau, state of Santa Catarina, Brazil, from 2006 to 2020. Clinical presentation, endovascular treatment, and postprocedure evolution to date are included.Case description Three children aged 5 to 12 months with cardiac, respiratory, or neurological damage in the neonatal stage, were referred to the neurosurgery service and diagnosed with VGAM. The three patients underwent endovascular embolization of the malformation, with different clinical evolution throughout outpatient follow-up.Conclusion Vein of Galen aneurysmal malformations are uncommon vascular abnormalities that, until the advent of endovascular embolization, were associated with high morbidity and mortality rates. Its prognosis is linked with initial clinic, early diagnosis, and timely surgical correction.
Keywords: arteriovenous malformations; intracranial aneurysm; vein of Galen; endovascular procedures; pediatrics; neurosurgery